IMF Survey, Volume 30, Issue 10. (IMF Survey; IMF Survey, 2001)
The IMF's Executive Board on May 15 approved an augmentation of Turkey's three-year Stand-By Arrangement by SDR 6.4 billion (about USD 8 billion), bringing the total to SDR 15 billion (about USD 19 billion). The full text of Press Release 01/23, including details of Turkey's economic program, is available on the IMF's website (www.imf.org).